New study skills training intervention for students who suffer from test anxiety - Motevalli, Saeid; Roslan, Samsilah; Sulaiman, Tajularipin; Hamzah, Mohd Sahandri Gani; Che Hassan, Norlizah; Garmjani, Maryam Gholampour (Canadian Center of Science and Education, 2013)
This article introduced a combination of study habits and test taking skills intervention for students on how to control test anxiety and promote their abilities and academic achievement. Based on skill-deficit model, anxious students suffer from test anxiety due to inability of using sufficient study habits and test taking skills to approach examination. Study skills interventions may assist anxious students to distinguish, recover and increase their study habits and test-taking skills. Study skills training intervention can improve students’ cognitive processes which affect the organization, processing and retrieval information. Study skills and test-taking skills training are two related treatment components of new study-skills training program. The present intervention introduced in this paper, attempts to guide students on the nature of anxiety, test anxiety, goal setting, motivation, time management techniques, memory tips, reading and summarizing skills improvement and test taking tricks. Through this intervention as a practical tool, students can be able to learn various tips and strategies across the study habits and test taking skills activities to improve their study abilities and academic achievement.